The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x

GATE2005-50

+3 votes
354 views

Let $G(x) = \frac{1}{(1-x)^2} = \sum\limits_{i=0}^\infty g(i)x^i$, where $|x| < 1$. What is $g(i)$?

  1. $i$
  2. $i+1$
  3. $2i$
  4. $2^i$
asked in Set Theory & Algebra by Veteran (13.6k points) | 354 views
Sumbody answer this ???b is the answer by putting x=0 but how to solve such types

Why don't use the same method?

https://en.wikipedia.org/wiki/Taylor_series

Yes but how to use compare them there are g(i) and Gx i know its easy but couldnt get it now

4 Answers

+11 votes
Best answer
$\frac{1}{1-x} = 1 + x + x^2 + x^3 + x^4 + x^5 + \dots + \infty$

Differentiating it w.r.to $x$

$\frac{1}{(1-x)^2} = 1 + 2x + 3x^2 + 4x^3 + 5x^4 + \dots + \infty$

$\sum_{i=0}^{\infty} g(i)x^i = g(0) + g(1)x + g(2)x^2 + g(3)x^3 + \dots + \infty$

Comparing above two, we get $g(1) = 2, g(2) = 3 \color{red}{\Rightarrow g(i) = i+1}$
answered by Veteran (27.6k points)
selected by

Direct application of formula if you know it.

+2 votes
We can use Maclaurin series $1/(1-x) = 1+x+x^{2}+x^{3}+x^{4}+...$

differentiating both side by x gives $1/(1-x)^{2} = 0+1+2x+3x^{2}+4x^{3}+...$

comparing this with given equaion $1/(1-x)^{2} = \sum g(i)x^{i} = g(0)+g(1)x+g(2)x^{2}+g(3)x^{3}+...$

$g(i)=i+1$

Option B
answered by Active (1.9k points)
+1 vote

Option B) is the answer 

answered by Boss (5.5k points)
0 votes

B is the correct option. Let us put values

S = 1 + 2x + 3x2 + 4x3 + ..........
Sx =    x  + 2x2 + 3x3 + .......... 
S - Sx = 1 + x + x2 + x3 + ....
S - Sx = 1/(1 - x) [sum of infinite GP series with ratio < 1 is a/(1-r)]
S = 1/(1 - x)2 

answered by Boss (5.4k points)


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

28,834 questions
36,688 answers
90,625 comments
34,641 users